Carbon Credits Through Wood Use: Revisiting the Maximum Potential and Sensitivity to Key Assumptions - Jari Niemi; Sampo Soimakallio; Elias Hurmekoski; Tanja Myllyviita; Janni Kunttu; Federico Lingua; Tord Snäll (GCB Bioenergy)
ABSTRACT Wood use generates technosphere carbon credits (TCCs) through avoided fossil‐based emissions and net sequestration of carbon into the technosphere (harvested wood products and geological storage). We investigated how large and uncertain TCCs of wood use per carbon harvested are considering the current and alternative ways of using wood, and the effects of the decarbonization of societies over 25‐, 50‐, and 100‐year time horizons. We applied stochastic simulation and scenario analysis using Finnish market structure as a baseline to demonstrate the use of the TCC calculator created. The mean value of TCCs of wood use were between 0.2 and 0.5 tC/tC with an uncertainty range from 0.1 to 0.8 tC/tC, depending on the scenario. The uncertainties were mainly concerned with the extent to which (1) fossil‐based emissions are avoided through substitution (displacement factors) and (2) fossil‐based raw materials are substituted (substitution rates). Assumptions on the decarbonization of societies reduced TCCs of wood use significantly over time. TCCs of wood use can be increased by directing wood into uses that substitute fossil‐intensive materials and have a long lifetime, such as construction materials, and increasing energy recovery and avoiding emitting carbon at the end of life of harvested wood products by carbon capture and storage. However, they were very likely to be considerably lower than forest carbon debits resulting from harvesting additional wood for substitution under all considered circumstances and under a wide but reasonable range of stochastic parameter values. Thus, the result emphasizes the need to reduce overall consumption of goods to mitigate climate change.